A multi-PMT optical sensor for IceCube-Gen2. (26th November 2021) - Basu, V.
Abstract: A new long optical module (LOM) is under development for IceCube-Gen2, the proposed expansion to the IceCube neutrino observatory at the South Pole. The module is housed in an elongated borosilicate-glass pressure vessel, the size of which is constrained by the borehole diameter, which impacts drilling economy. The designs under consideration use either 16 or 18 4-inch PMTs, conditional on future performance tests, mounted so as to guarantee full angular coverage. Modular electronics have been custom-designed to fit into the available space and to minimize cost and power requirements for the ∼10000 modules to be installed. We will provide an overview of our approach to these design considerations and summarize the results of our tests and simulations. Prototype modules will be installed in the upcoming IceCube Upgrade.